Topical issues on the formation of professional legal consciousness of a judge - Abdrasulov Е.Б.; Saktaganova А.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
Research concerning formation of professional legal consciousness of judges occupies a vital place within modern legal systems. Studies are undertaken in this regard in order to explore processes and mechanisms underlying formation, while simultaneously analyzing their effect on quality and efficiency of judiciary services. This study seeks to identify, analyse and systematise factors contributing to the formation and development of professional legal consciousness among judges. Research efforts will mainly involve studying theoretical aspects of legal consciousness; reviewing existing approaches used for education and practical training of judges; as well as measuring its effect on developing professional legal consciousness over time through practice judicial examination. Scientific and practical relevance lies within this work’s significance for understanding processes that form judges’ legal consciousness, essential for improving judicial system quality. Methodologies employed include comparative analysis, investigation of normative documents and court practice as well as empirical methods. The main results of this research include identification and recommendations of key influences affecting judges’ legal consciousness formation, with particular attention paid to how those factors interact with one another. Finally, its conclusions emphasize the necessity of taking an integrated approach when training and developing judges involving both theoretical and practical activities. This study’s value lies in its contribution to understanding how judges form professional legal consciousness that ultimately improves justice delivery and strengthens rule of law. Furthermore, its practical significance manifests itself by producing specific recommendations designed to increase professionalism and efficiency within judicial systems.